Correlation between the clinicopathological features and prognosis in patients with extranodal natural killer/T cell lymphoma - Lin-Shu Zeng (KeAi Communications Co., Ltd., 2017)
Objective: To investigate the correlation between the clinicopathological features and prognosis in patients with extranodal natural killer (NK)/T-cell lymphoma (ENKTCL). Methods: One hundred and four patients diagnosed with ENKTCL at the Department of Pathology, Cancer Hospital, Chinese Academy of Medical Sciences, Beijing, China from November 1991 to September 2011 were included in the study. The clinicopathological features and their correlations with disease prognosis were evaluated in these patients. Results: The number of effective follow-up cases was 56 (53.8%) by the end of last follow-up in October 2015. Univariate survival analysis showed that granzyme B, perforin, and Bcl-2 expression was significantly associated with a poor prognosis in ENKTCL (P = 0.033, 0.004, and 0.034, respectively), whereas platelet-derived growth factor receptor-alpha (PDGFRA) expression was significantly associated with a better prognosis (P = 0.034). Ki-67 overexpression (≥50%) was significantly associated with a poor prognosis (P = 0.017). Different treatment approaches were also associated with prognosis (P = 0.014); specifically, the efficacies of combination treatments including chemotherapy and radiotherapy, and autologous hematopoietic stem cell transplantation were significantly better than those involving radiotherapy and chemotherapy alone. Patient gender, age, tumor location, staging, the presence of B symptoms, pretreatment lactate dehydrogenase levels, and β2-microglobulin levels were not associated with the prognosis of ENKTCL (P > 0.05). However, multivariate analyses showed that the treatment approach and all the immune markers were not independent prognostic factors for ENKTCL. Conclusion: Granzyme B, perforin, and Bcl-2 expression and Ki-67 overexpression (≥50%) might be adverse prognostic factors for ENKTCL, whereas PDGFRA-positivity suggested a better disease prognosis. In addition, different treatment approaches might be closely related to patient prognosis.